Tracing Variation in Diagenesis in Concretions: Implications from a Raman Spectroscopic Study - Han, Yaxuan; Shimooka, Kazuya; Yeh, Meng-Wan; Tsuboi, Motohiro (Minerals (Basel), 2025)
Concretions represent an exceptional mode of fossil preservation. This is attributed to their mineralized outer mantle, which exhibits low permeability and porosity, thereby limiting diagenetic alteration. The present research employs microscopic Raman spectroscopy to assess the thermal maturity of kerogen—a highly sensitive organic material—within concretions from northeast Taiwan. Comparative analysis of kerogen from the concretion’s core, rim, and surrounding matrix reveals differential preservation states. The organic matter in the core remains relatively unaltered, whereas the rim exhibits partial graphitization, albeit to a lesser extent than the surrounding matrix. These findings indicate a progressive diagenetic gradient, with the core influenced by the least thermal alteration, followed by the rim, and the surrounding matrix that experiences the highest degree of graphitization. Therefore, the present research underscores the role of concretionary encapsulation in mitigating diagenetic modification and enhancing organic matter preservation.